Industrial Heating application of a Salinity gradient solar pond for salt production. (February 2019) - Bawahab, Mohammed; Faqeha, Hosam; Ve, Quoc Line; Faghih, Ahmadreza; Date, Abhijit; Akbarzadah, Aliakbar
Abstract: This research is investigating the possibility of using heat stored in solar ponds for salt drying. At present, Pyramid Salts, a salt producing company located in the north of Victoria, Australia, use electric heaters to heat ambient air from around 20 °C to around 70 °C in their salt crystallizers for salt drying. This research paper aims to develop a solar PV driven heat pump coupled with a solar pond to supply necessary hot air. According to the collected data solar pond performance in Pyramid Hill indicates that heat will be available at the bottom of the pond between 35 °C to 50 °C (winter to summer). Coupling the salinity gradient solar pond with the heat pump is the novelty of this research paper. The heat pump's evaporation boosts from ambient temperature to available solar pond heat (40 °C) and above 24/7 all year around. As a result, the amount of electrical energy saving in this project has been estimated to be about 1 GWh per year. In this work, the preliminary data on the developments of salinity, temperature, and turbidity profiles will be considered and discussed.